PERANCANGAN MOTON GRAPHIC BAHAYA GAME ONLINE BAGI REMAJA KOTA PADANG - LIYA SARI, Dini Faisal, S.Ds., M.Ds., Drs. Syafwan, M.Si. (DEKAVE : Jurnal Desain Komunikasi Visual, 2019)
The purpose of this design is to provide encouragement to teens in overcoming the dangers of playing excessive online games. The design method used is the glass box method which is a rational and logical design, and through several stages that are considered by the designer.Designing interesting and well-conveyed motion graphics, the designer conducts research and data collection by observing, interviewing and studying literature. With this problem the solution to overcome the dangers of online games in adolescents is to socialize audio visual form of motion graphics about the dangers of playing online games for adolescents in the city of Padang. This design is supported by several supporting media such as: Poster, T-shirt, Totebag, Key Chain, Sticker, Notebook, CD Cover and CD Label.Kata Kunci : Motion Graphic, Game Online, ILM, a Teenager, Padang City.